Islam Moderat sebagai Retorika Populisme Aktor Politik: Semiotika Akun @CakIminNow - Sriharyani, Yuni (Jurnal Komunikasi Islam, 2024)
This study examines the populist rhetoric of political actor, Muhaimin Iskandar, delivered on @CakIminNow during the 2024 Indonesian presidential election campaign, especially in the tweet dated October 1, 2023 regarding the Celebration of Pancasila Sanctity Day. This study uses a critical paradigm and Roland Barthes’ semiotic analysis technique in analyzing nine units of analysis posted on @CakIminNow. The results of this study have revealed that the representation of moderate Islam has been utilized as a tool of populist rhetoric by Muhaimin Iskandar (Cak Imin) as one of the vice presidential candidates in the 2024 election. In addition, moderate Islam is not only seen as a system of beliefs and religious practices but also as a commodity in political marketing communication efforts by political actors. In short, this populist rhetoric functions as a strategy to strengthen the political image and garner voter support during Indonesia’s 2024 presidential election campaign.